Realization of Minimum and Maximum Gate Function in Ta(2)O(5)-based Memristive Devices - Breuer, Thomas (Sci Rep, 2016)
Redox-based resistive switching devices (ReRAM) are considered key enablers for future non-volatile memory and logic applications. Functionally enhanced ReRAM devices could enable new hardware concepts, e.g. logic-in-memory or neuromorphic applications. In this work, we demonstrate the implementation of ReRAM-based fuzzy logic gates using Ta(2)O(5) devices to enable analogous Minimum and Maximum operations. The realized gates consist of two anti-serially connected ReRAM cells offering two inputs and one output. The cells offer an endurance up to 10(6) cycles. By means of exemplary input signals, each gate functionality is verified and signal constraints are highlighted. This realization could improve the efficiency of analogous processing tasks such as sorting networks in the future.